Safety Behavior of Medical Staff in Hospital Tourism - Sentot, Bambang Jati; Suhud, Usep; Buchdadi, Agung Darmawan (Migration Letters, 2023)
Medical staff are critical to the success of hospital tourism services. There is a relationship between the medical staff and medical tourists, particularly in terms of scope of care, quality of care, communication, service coordination, cultural sensitivity, legal and ethical considerations. The purpose of this study is to identify factors influencing the success of medical tourism services in terms of safety behavior of medical staff in providing medical services, and the influence of medical staff’s safety knowledge, safety motivation, and safety climate on the safety behavior of medical staff in providing hospital tourism services. This study employed a mixed method of convergent model in a quantitative manner by utilizing a probability sampling method and a basic random sampling method. The data was obtained through questionnaires distributed to 12 of 20 JCI-accredited hospitals in Indonesia. There was a total of 200 respondents, but only 124 of them completed the questionnaire. The data was analyzed using Structural Equation Modeling (SEM). The results show that the safety knowledge, safety motivation, and safety climate influence the safety behaviour of medical staff in providing the hospital tourism services.